Thoracic Wall Reconstruction in Advanced Breast Tumours - Daigeler, A.; Harati, K.; Goertz, O.; Hirsch, T.; Behr, B.; Lehnhardt, M.; Kolbenschlag, J. (Geburtshilfe und Frauenheilkunde, 2014)
In advanced mammary tumours, extensive resections, sometimes involving sections of the thoracic wall, are often necessary. Plastic surgery reconstruction procedures offer sufficient opportunities to cover even large thoracic wall defects. Pedicled flaps from the torso but also free flap-plasties enable, through secure defect closure, the removal of large, ulcerated, painful or bleeding tumours with moderate donor site morbidity. The impact of thoracic wall resection on the respiratory mechanism can be easily compensated for and patientsʼ quality of life in the palliative stage of disease can often be improved.
Keywords: deformities of the breast; breast; breast cancer; breast carcinoma